2012
DOI: 10.1017/s1041610212001548
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural ageism: ageism and attitudes toward aging among Jews and Arabs in Israel

Abstract: Our findings point that the cultural importance of elders for the Arab cohort transcends beyond Westernization processes which affect the Arab society in Israel, and reflect the demanding role of Arab women as primary caregivers for the elders in the family. Limitations and implications of the study are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 22 publications
1
41
0
Order By: Relevance
“…For example, stereotypic beliefs about aging and older adults have been shown to be related to increased aging anxiety (Bousfield & Hutchison, ) and this may moderate the relationship between aging anxiety and job longevity variables, particularly if one has negative perceptions of aging. Aging anxiety, while weakly related to job longevity variables, should continue to be investigated, especially with regard to other variables such as individual differences, particularly since findings from this study and past research has suggested that females and racial/ethnic minorities tend to report more aging anxiety (Bergman, Bodner, & Cohen‐Fridel, ; Lynch, ).…”
Section: Discussionmentioning
confidence: 84%
“…For example, stereotypic beliefs about aging and older adults have been shown to be related to increased aging anxiety (Bousfield & Hutchison, ) and this may moderate the relationship between aging anxiety and job longevity variables, particularly if one has negative perceptions of aging. Aging anxiety, while weakly related to job longevity variables, should continue to be investigated, especially with regard to other variables such as individual differences, particularly since findings from this study and past research has suggested that females and racial/ethnic minorities tend to report more aging anxiety (Bergman, Bodner, & Cohen‐Fridel, ; Lynch, ).…”
Section: Discussionmentioning
confidence: 84%
“…A study involving 275 medical students by Taiwan researchers indicated that the KAOP score was 144.3 ± 17.89 and >50% in medical students [23]. Bergman et al [28] reported that Chinese nursing students had more positive attitudes towards the elderly than Australian nursing students. Our results suggest that Chinese medical students have more positive attitudes towards the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the strong influence of culture on gender roles and aging processes (e.g., Bergman et al 2013;Kamilar et al 2000), it would be an interesting avenue for future research to investigate the role of culture on the interplay of the perceptions of older men and women.…”
Section: Discussionmentioning
confidence: 99%